The first Advent in Palestine reversals, resistance, and the ongoing complexity of hope - Nikondeha, Kelley, 1969- (Broadleaf Books, 2022)
Bringing us the untold--often hidden--story of Advent, Kelley Nikondeha takes us back to the original landscapes. Then, as now, Palestine was the geographic, socioeconomic, and political backdrop of the Gospel narratives that wrestle with dark themes of violence, exploitive economics, and abuse to arrive at the hard-won hope of Jesus's birth.